Comparative evaluation of McCoy laryngoscope and The Anaesthetist Society Scope for intubation in patients with anticipated difficult airway - Raghavendra Prasad Saya; Vijaya Durga Somula; Muneer Ahmed Tappa; Balaji Tharigonda; Sunil Chiruvella (The Indian Anaesthetists' Forum)
Background and Aim: McCoy laryngoscope and video laryngoscopes (VLS) are being increasingly used in practice as they offer advantages over Macintosh laryngoscope in the management of difficult airway. The present study was aimed at comparing McCoy laryngoscope and The Anaesthetist Society Scope (TAScope) VLS regarding ease of intubation using Intubation Difficulty Scale (IDS) score in patients with an anticipated difficult airway. Methods: A total of 80 patients of either sex, belonging to the American Society of Anesthesiologists physical status I and II, undergoing surgery under general anesthesia and having simplified airway risk index score of 4 and above were randomized to two groups, McCoy group (n = 40) and TAScope group (n = 40). The primary objective of the study was to compare ease of intubation using IDS score in both the groups. Secondary objectives included time for intubation (TI), hemodynamic stress response, and incidence of oropharyngeal trauma. Results: Mean IDS score was significantly lower in TAScope group in comparison to McCoy group (0.9 ± 1.35 vs. 3.57 ± 2.46, P < 0.0001). The need for multiple intubation attempts, laryngeal pressure, and excess lifting force was significantly less in TAScope group (P = 0.0493, P = 0.0001 and P = 0.0007, respectively). TI was significantly longer in TAScope group in comparison to McCoy group (45.27 ± 6.06 s vs. 30.95 ± 9.13 s, P < 0.0001). The incidence of oropharyngeal trauma and hemodynamic changes was comparable in both the groups. Conclusion: TAScope is superior to McCoy laryngoscope for intubation in adult patients with anticipated difficult airway as it improves glottic view and facilitates easy intubation.